2014
DOI: 10.1039/c4sm00484a
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear microrheology of lysozyme layers forming at the air–water interface

Abstract: We report experiments studying the mechanical evolution of layers of the protein lysozyme adsorbing at the air-water interface using passive and active microrheology techniques to investigate the linear and nonlinear rheological response, respectively. Following formation of a new interface, the linear shear rheology, which we interrogate through the Brownian motion of spherical colloids at the interface, becomes viscoelastic with a complex modulus that has approximately power-law frequency dependence. The pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Specifically, as a function of the number density of the proteins at the interface, the surface diffusion coefficient obeys a Vogel-Fulcher-Tamann law. This is consistent with the microrheology experiments on the viscoelastic behavior of protein layers 64,65 .…”
Section: Methodssupporting
confidence: 91%
“…Specifically, as a function of the number density of the proteins at the interface, the surface diffusion coefficient obeys a Vogel-Fulcher-Tamann law. This is consistent with the microrheology experiments on the viscoelastic behavior of protein layers 64,65 .…”
Section: Methodssupporting
confidence: 91%
“…9,15,17,18,44,45 Additionally, it has been established that lysozyme responds differently to active versus passive microrheology. 46,47 Perhaps the soft cluster glass, that forms as a result of the weak temporary bonds induced by the SALR potential, locally shear-melts already at the low shear stress induced by the active microrheology experiment.…”
Section: Resultsmentioning
confidence: 99%
“…2,[20][21][22][23][24] The impact of the chemical properties of the hydrophobic subphase is widely neglected and systematic studies are missing, even though a small number of publications indicated changes in interfacial processes at different hydrophobic interfaces. 23,[25][26][27][28][29][30] Globular proteins, such as β-lactoglobulin (BLG), bovine serum albumin (BSA), and hen egg white lysozyme (LSZ), consist of an amino acid chain which arranges into a well-defined secondary and tertiary structures. In water, they have a sphere-like native configuration with most of their hydrophilic amino acid groups at the exterior and hydrophobic residues located at the interior.…”
Section: Introductionmentioning
confidence: 99%